2003
DOI: 10.1128/iai.71.1.567-570.2003
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Emetic Response to Staphylococcal Enterotoxins in the House Musk Shrew ( Suncus murinus )

Abstract: The emetic responses induced by staphylococcal enterotoxin A (SEA), SEB, SEC2, SED, SEE, SEG, SEH, and SEI in the house musk shrew (Suncus murinus) were investigated. SEA, SEE, and SEI showed higher emetic activity in the house musk shrew than the other SEs. SEB, SEC2, SED, SEG, and SEH also induced emetic responses in this animal model but relatively high doses were required. The house musk shrew appears to be a valuable model for studying the mechanisms of emetic reactions caused by SEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 30 publications
3
83
0
2
Order By: Relevance
“…For example, it has been shown that different types of SEs have different emetic response activities in house musk shrews, although it was thought that there are no differences in the emetic response activities of SEA, SEB, SEC, SED, and SEE in humans and primates (18). In addition, S. aureus expression of specific ent genes may depend on the host tissue and may play a role in the adaptation of S. aureus to the host environment (4).…”
Section: Vol 42 2004 Simultaneous Analysis Of Multiple Se Genes 2141mentioning
confidence: 99%
“…For example, it has been shown that different types of SEs have different emetic response activities in house musk shrews, although it was thought that there are no differences in the emetic response activities of SEA, SEB, SEC, SED, and SEE in humans and primates (18). In addition, S. aureus expression of specific ent genes may depend on the host tissue and may play a role in the adaptation of S. aureus to the host environment (4).…”
Section: Vol 42 2004 Simultaneous Analysis Of Multiple Se Genes 2141mentioning
confidence: 99%
“…Although a few clinical studies have attempted to correlate toxic shock and outcome with the presence of certain SEs in patients with S. aureus infections (Kravitz et al 2005;Ferry et al 2008), the contribution of these toxins to outcome is still unclear. With new data emerging implicating SEs in the pathogenesis of chronic allergic syndromes, production of monoclonal antibodies and vaccine strategies targeting SEs may be considered (Bonventre et al 1988;LeClaire et al 2002;Hu et al 2003;Kansal et al 2007) in the future. It is therefore important to characterize the prevalence of SE and SCCmec genes in clinical S. aureus strains.…”
mentioning
confidence: 99%
“…Uważa się, że najwyższą wrażliwością charakteryzuje się człowiek (6). Obecnie do badań wykorzystuje się małpy Macaca fascicularis oraz ryjówka domowego (Suncus murinus), ssaka należącego do rodziny ryjówkowatych (15,28). Wykorzystywanie małp wiąże się z wysokimi kosztami i pociąga za sobą wątpliwości natury etycznej.…”
Section: Aktywność Wymiotna Enterotoksyn Gronkowcowychunclassified
“…Prace przeprowadzone przez Hu i wsp. (15) na Suncus murinus wykazały znaczące zróżnicowanie efektu wymiotnego białek rodziny enterotoksyn. W wyniku dootrzewnowej iniekcji toksyn wykazano, że dawki indukujące wymioty u ryjówka domowego są istotnie niższe dla SEA, SEE i SEI w porównaniu do SEB, SEC 2 , SED, SEG oraz SEH.…”
Section: Aktywność Wymiotna Enterotoksyn Gronkowcowychunclassified